Solve the simultaneous equation by Cramer’s rule 6x – 4y = -12 , 8x – 3y = -2 Question Solve the simultaneous equation by Cramer’s rule 6x – 4y = -12 , 8x – 3y = -2 in progress 0 Math Piper 4 weeks 2021-11-02T07:09:35+00:00 2021-11-02T07:09:35+00:00 1 Answer 0 views 0

## Answers ( )

6x – 4y = -12

8x – 3y = -2

D = | 6 -4 |. D = (-18 +32) = 14

| 8 -3 |

Dx = | -12 -4 |. Dx = (36 – 8) = 28

| -2 -3 |

Dy = | 6 -12 |. Dy = (-12 + 96) = 84

| 8 -2. |

X = (Dx/D) = (28/14) = 2

Y = (Dy/D) = (84/14) = 6

so, X = 2 and Y = 6